Measurement of the W±Z boson pair-production cross section in pp collisions at s√=13 TeV with the ATLAS Detector - Aaboud, M. (2016)
The production of events in proton–proton collisions at a centre-of-mass energy of is measured with the ATLAS detector at the LHC. The collected data correspond to an integrated luminosity of . The candidates are reconstructed using leptonic decays of the gauge bosons into electrons or muons. The measured inclusive cross section in the detector fiducial region for leptonic decay modes is . In comparison, the next-to-leading-order Standard Model prediction is . The extrapolation of the measurement from the fiducial to the total phase space yields , in agreement with a recent next-to-next-to-leading-order calculation of . The cross section as a function of jet multiplicity is also measured, together with the charge-dependent and cross sections and their ratio.